Integrating forests and biodiversity in Nepal's National Adaptation Plan: A review and synthesis of knowledge stock on opportunities and way forward - Karki, G.; Paudel, B.; Uprety, B. K. (Banko Janakari, 2018)
Climate change brings lasting changes in forests and biodiversity together with the ecosystem services altering its ability to support present and future economic activities. Current forest utilization and preservation is based on how forests developed under past climatic conditions. Policy-makers and forest managers must accept that climate change is inevitable and from which forests and forest communities are significantly impacted globally and in Nepal also, sustainable forest management (SFM) is already based on many measures to adapt to climate change as planned adaptation will reduce vulnerability at intervened sites and will have long term impacts. However, many forest species will be adapting autonomously and society will have to adjust to the result. Adaptation requires planning for change so that a suite of options for the future but based on the present practice and knowledge is to be available whenever needed. On the foundation of concurrent learning, knowledge and experiences of National Adaption Program of Action (NAPA) process, the National Adaptation Plan (NAP) process for forests and biodiversity will build medium and long-term adaptation strategies and plans with widely accepted objectives of future forests and biodiversity management. Banko Janakari A Journal of Forestry Information for Nepal Vol. 27, No. 2, 2017, page: 21-31